3-Hydroxypropionic acid contributes to the antibacterial activity of glycerol metabolism by the food microbe Limosilactobacillus reuteri - Liang, Nuanyi; Neužil-Bunešová, Věra; Tejnecký, Václav; Gänzle, Michael; Schwab, Clarissa (Food microbiology, 2021)
Strains of Limosilactobacillus reuteri are used as starter and bioprotective cultures and contribute to the preservation of food through the production of fermentation metabolites lactic and acetic acid, and of the antimicrobial reuterin. Reuterin consists of acrolein and 3-hydroxypropionaldehyde (3-HPA), which can be further metabolized to 1,3-propanediol and 3-hydroxypropionic acid (3-HP). While reuterin has been the focus of many investigations, the contribution of 3-HP to the antimicrobial activity of food related reuterin-producers is unknown. We show that the antibacterial activity of 3-HP was stronger at pH 4.8 compared to pH 5.5 and 6.6. Gram-positive bacteria were in general more resistant against 3-HP and propionic acid than Gram-negative indicator strains including common food pathogens, while spoilage yeast and molds were not inhibited by ≤ 640 mM 3-HP. The presence of acrolein decreased the minimal inhibitory activity of 3-HP against E. coli indicating synergistic antibacterial activity. 3-HP was formed during the growth of the reuterin-producers, and by resting cells of L. reuteri DSM 20016. Taken together, this study shows that food-related reuterin producers strains synthesize a second antibacterial compound, which might be of relevance when strains are added as starter or bioprotective cultures to food products.
Keywords: Glycerol; Drug Stability; fermentace; glycerol; Antibacterial; Lactobacillaceae; Lactic Acid; Anti-Infective Agents; antiinfekční látky; Food Microbiology; Fermentation; Reuterin; Limosilactobacillus reuteri; kyselina octová; Glyceraldehyde; Acetic Acid; Hydrogen-Ion Concentration; 3-Hydroxypropionic acid; stabilita léku; Bacteria; glyceraldehyd; koncentrace vodíkových iontů; kyselina mléčná; propan; Antifungal; potravinářská mikrobiologie; Propane